Furosemide for prevention of morbidity in indomethacin‐treated infants with patent ductus arteriosus - Brion, Luc P (Cochrane Database Syst Rev, 2001)
BACKGROUND: Inhibition of prostaglandin synthesis mediates closure of the ductus arteriosus and renal side effects after indomethacin administration. Because furosemide increases prostaglandin production, it could potentially help prevent indomethacin‐related toxicity, but also decrease ductal response to indomethacin. OBJECTIVES: The primary objectives of this review were to assess (1) whether furosemide affects the incidence of failure of ductal closure after indomethacin and that of indomethacin‐related toxicity and (2) the effect of furosemide on mid‐term and long‐term outcome. The secondary objective was to determine whether the effect of furosemide on renal function and water balance depends on prior extracellular volume (assessed by blood urea nitrogen [BUN]/creatinine ratio). SEARCH METHODS: Electronic databases (MEDLINE, EMBASE and the Cochrane Central Register of Controlled Trials (CENTRAL, The Cochrane Library) and selected abstract books, without language restriction were searched. For the latest update, database searches were done on April 1, 2007 and Issue 1, 2007 of The Cochrane Library. SELECTION CRITERIA: Studies with (1) random allocation to either indomethacin alone or indomethacin and furosemide and (2) analysis of either short‐term risk‐benefit ratio of furosemide, mid‐ or long‐term outcome, or the relationship between extracellular volume at study entry and changes in renal function were selected. DATA COLLECTION AND ANALYSIS: Studies were assessed for possible bias and for quality of assessment of ductal patency. Categorical variables were assessed using relative risk and absolute risk reduction. The effects of furosemide on renal function and fluid balance were assessed by comparing changes from baseline in the treatment group with those in controls. Subsets were determined a priori based on BUN/creatinine ratio at study entry. MAIN RESULTS: All three studies fulfilling the entry criteria had limitations, including possible or definite bias. There was substantial heterogeneity among studies.   Furosemide administration did not significantly increase the risk of failure of ductal closure; however, sample size was insufficient to rule out even a 31% increase. In the subset with initial BUN/creatinine ratio > 20 mg/mg, two of 18 patients receiving furosemide could not complete a three‐dose course of indomethacin because of toxicity. Minimal or no information was available about any of the other main outcome variables. Furosemide increased urine output regardless of the initial BUN/creatinine ratio, leading to a 5% weight loss during a three‐dose course, an undesired effect in patients with initial BUN/creatinine ratio > 20 mg/mg. Furosemide increased creatinine clearance only in patients with initial BUN/creatinine ratio < 20 mg/mg. AUTHORS' CONCLUSIONS: There is not enough evidence to support the administration of furosemide to premature infants treated with indomethacin for symptomatic patent ductus arteriosus. Furosemide appears to be contraindicated in the presence of dehydration in those infants.